1st International Conference on Global Issue for Infrastructure, Environment & Socio-Economic Development. (February 2019) - Unknown
Abstract : PREFACE The 1 st International Conference on Global Issue for infrastructure, environment & socio-economic development (IC-GIESED 2018) was held in Makassar, Indonesia on September 31 - October 1, 2018. IC-GIESED 2018 is dedicated to address issues related to natural disaster management on risk reduction toward sustainable development for civic society, hosted by Post Graduate School of Hasanuddin University and Publication Management Centre (PMC), Hasanuddin University. Natural disaster still becomes a global issue in the world, particularly, Indonesia. The major goal and feature of the conference was to promote knowledge, science, and technology as well as to address issues in natural disaster, by bringing together researchers, scientists, practitioners and scholars in the respected fields. Professors from Japan and Australia are invited to deliver keynote speeches, together with invited speakers from Philippine, Malaysia, Netherlands and Indonesia. Their presence indicates the concern and role of the researchers, scientists and practitioners which are significant in keeping Global Issue for infrastructure, environment & socio-economic development. This proceedings present selected papers submitted to the conference by academics and researches from universities and research institutes. All papers were subjected to rigorous peer-reviews by conference committee members and international reviewers to ensure their compliance to meet the required standard for qualified scientific publication. This volume presents recent researches in the field of Global Issue for infrastructure, environment & socio-economic development covering various related areas: disaster analysis, disaster monitoring and mitigation, emergency preparedness, risk mitigation, risk and security, safety and resilience, socio-economic issues, health risk, infrastructure & environment, human factors and multi-hazard risk assessment We would like to appreciate all authors who have contributed to this proceedings, the conference committee, speakers, attendees, organizing committee and sponsors who have made the 1 st GIESED 2018 a succces. We wish the conference will have siginificant contribution in field of global issue for infrastructure, environment & socio-economic development. We are also expecting that this conference proceeding contributes in looking at a new paradigm for global Issue for infrastructure, environment & socio-economic development. Herman Parung Chair of Organizing Commitee GIESED 2018. Muhammad Arsyad Director of Publication Management Centre Hasanuddin University